DEVELOPMENT OF THE FUTURE TRANSLATORS' PROFESSIONAL COMPETENCY IN BILATERAL INTERPRETING: MODERN METHODS - Alla Bogush; Tetiana Korolova; Oleksandra Popova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The paper presents the research on the effectiveness of the future translator and / or interpreter training using modern methods which facilitate the development of their professional competency in bilateral interpreting. The authors analyse psychological and pedagogical experience, modern educational technologies and prospects for future professionals in the context of bilateral interpreting. The scholars substantiate the results of the initiated phonetic research (including linguistic and translation analysis of audio texts) related to the semantics of prosodic means, which constituted the basis for the experimental study. The research reveals the outcomes of the experimental study conducted at Ushynsky University involving the third-year students who major in the English↔Ukrainian translation. The four stages of the designated pedagogical experiment are specified: 1) pre-testing; 2) preparatory training course according to combined (interactive and traditional) authors' teaching methods; 3) after-testing; 4) assessment of the students' outcomes. The use of the experimental construct turns out to be practical due to these methods: cooperative learning, inquiry-based instructions, differentiation, professional development, technology and problem solving. The study also confirms the fact that the integration of traditional and modern technologies in teaching students to interpret information taking into consideration phonetic features of Ukrainian and English oral texts can help future translators develop their analytical and critical thinking, flexibility, agility and adaptability, initiative and entrepreneurialism while receiving, analysing and interpreting information. The detailed analysis of modern scientific literature proves that the use of the competence-oriented and context-centred approaches to the educational process contributes to the students' academic success.